Health Coaching Based on Social Cognitive Theory in Increasing Compliance with Fluid Restrictions, Controlling Interdialytic Weight Gain and Improving the Quality of Life of Hemodialysis Patients - Arie Kusumo Dewi; Ima Nadatien; Raden Khairiyatul Afiyah (Universitas STRADA Indonesia, 2025)
Background: Chronic kidney failure requires long-term treatments like hemodialysis, a vital therapy for managing the disease. Patient compliance with fluid restrictions and controlling interdialytic weight gain (IDWG) significantly impacts therapy effectiveness. Health coaching based on social cognitive theory may enhance understanding, motivation, and healthy behaviors in hemodialysis patients. Purpose: This study aims to analyze the impact of health coaching based on social cognitive theory on compliance with fluid intake restrictions, IDWG control, and quality of life in chronic kidney failure patients undergoing hemodialysis. Methods: A quasi-experimental study with a pre-post test control group design involved 38 hemodialysis patients selected via simple random sampling. The intervention group received social cognitive theory-based health coaching sessions for four weeks, while the control group received standard care following hospital procedures. Data collection included daily fluid restriction records, IDWG measurements, and a validated quality of life questionnaire, with pre- and post-intervention comparisons. Results: The intervention group demonstrated a significant improvement in compliance with fluid restrictions (p < 0.011), better IDWG control (p < 0.021), and enhanced quality of life (p < 0.001) compared to the control group. Conclusion: Health coaching based on social cognitive theory effectively improves fluid restriction compliance, reduces IDWG, and enhances the quality of life in hemodialysis patients. Integrating this approach into routine hemodialysis care can optimize therapeutic outcomes and significantly benefit patients.